Evaluation of endometrial immune status of polycystic ovary syndrome. (April 2021) - Liu, Su; Hong, Ling; Mo, Meilan; Xiao, Shan; Chen, Cong; Li, Yuye; Lian, Ruochun; Wang, Xuejin; Cai, Songchen; Diao, Lianghui; Zeng, Yong
Highlights: Women with PCOS have altered endometrial immune cells, which may reflect a state of chronic low grade inflammation. Decreased endometrial CD56 + NK cells and CD163 + M2 macrophages were correlated with insulin resistance in PCOS. Endometrial CD83 + mDCs was correlated with the degree of hyperandrogenemia in the whole study population. Abstract: Polycystic ovary syndrome (PCOS) is described as a low-grade chronic inflammatory state. However, there are limited studies on the specific endometrial immune status of PCOS patients. Whether this endometrial immune cell pattern is intrinsic to PCOS or the consequence of PCOS-associated obesity is a subject of debate. This study retrospectively included one hundred women diagnosed with PCOS and ninety-five normal fertile controls, which further divided into four groups (normoweight PCOS; overweight PCOS; normoweight control; overweight control) based on body mass index. The percentages of endometrial CD68 + macrophages (1.97 % vs. 1.17 %; P < 0.001), CD163 + M2 macrophages (2.30 % vs. 1.83 %; P = 0.001), CD1a + iDCs (0.044 % vs. 0.029 %; P = 0.002), CD83 + mDCs (1.72 % vs. 1.07 %; P < 0.001) and CD8 + T cells (2.82 % vs. 1.95 %; P < 0.001) were significantly higher in normoweight PCOS women than normoweight controls. The percentage of CD68 + macrophages (2.09 % vs. 1.15 %; P < 0.001) was significantly higher in overweight PCOS women compared with overweight controls. In multivariant linear regression analysis, participants' PCOS status was the main predictors of endometrial CD68 + macrophages, CD163 + M2 macrophages, CD1a + iDCs, CD83 + mDCs and CD8 + T cells in the whole study population. Additionally, in PCOS group, positive correlations were found between endometrial CD56 + NK, CD163 + M2 macrophages and QUICKI, indicating there was an association between endometrial immune cells and insulin resistance in PCOS women. Our study suggests that women with PCOS have altered endometrial immune cells, which may reflect a state of chronic low grade inflammation. The chronic inflammation, independent of obesity, may help understand the pathophysiologic mechanisms of intrinsic PCOS.